2011
DOI: 10.1111/j.1365-3164.2011.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological efficacy and stability of diluted ticarcillin–clavulanic acid in the topical treatment of Pseudomonas aeruginosa infections

Abstract: Topical compounded Timentin(®) diluted with an inactive vehicle has been reported to be effective in the treatment of otitis externa caused by Pseudomonas aeruginosa. The aims of this study were to determine the biological efficacy of Timentin(®) (ticarcillin and clavulanic acid) when diluted in the carrier vehicle Methopt(®) against P. aeruginosa and to determine the efficacy and stability of Timentin(®) aqueous stock concentrate solution. Timentin(®) stock concentrate was tested against four P. aeruginosa is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Otitis is believed to be multifactorial and treatment can be difficult in some cases. [1][2][3] Common organisms isolated from dogs with otitis externa include Staphylococcus spp., Pseudomonas spp., Proteus spp., Streptococcus spp., Escherichia coli, Klebsiella spp., Bacteroides spp., Pasteurella spp. and Malassezia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Otitis is believed to be multifactorial and treatment can be difficult in some cases. [1][2][3] Common organisms isolated from dogs with otitis externa include Staphylococcus spp., Pseudomonas spp., Proteus spp., Streptococcus spp., Escherichia coli, Klebsiella spp., Bacteroides spp., Pasteurella spp. and Malassezia spp.…”
Section: Introductionmentioning
confidence: 99%
“…The stability and efficacy of the ticarcillin used in this way was investigated in a further study (Bateman et al . ). This work indicated that storage of the ticarcillin stock solution at −20°C does not compromise efficacy for at least 12 months.…”
Section: Topical Therapy To Manage Secondary Causes Of Otitismentioning
confidence: 97%
“…These are fluoroquinolones, such as marbofloxacin, and aminoglycosides, particularly gentamicin and polymyxin B. Topical otic treatments containing antibiotics with marketing authorisation in the UK are shown in Table 2. In addition, some clinicians prepare ad hoc solutions using injectable solutions of antibiotics when resistance is seen or suspected [58] e.g., ticarcillin-clavulanic acid [59], amikacin [60], ceftazidime [61], and enrofloxacin [62]. There is a perception that such mixtures may be less ototoxic in the case of a ruptured tympanic membrane, but this is not substantiated in the literature [63].…”
Section: Treatmentmentioning
confidence: 99%